Preparation and lithium storage performance of SiO2/Ag composite materials coated with polyphosphazene - Zhengping Zhao; Zhao Xu; Zhong Zheng; Wei Wang; Wenyu Wang; Xingcheng Yang; Siqi Zhu; Jia Wei Chew (eXPRESS Polymer Letters)
Lithium-ion batteries (LIBs) are widely used as important energy storage and energy supply devices. The porous design and heteroatomization modification of carbon-based anode materials are crucial for achieving high-capacity and reversible energy storage in LIBs. Sol-gel method and pyrolysis treatment were used to obtain silica/silver composite particles used as templates. Polyphosphazene-coated silica/silver composite composite carbon materials (SiO2/Ag@PZS-C) were synthesized through in-situ self-assembly and carbonization of polyphosphazene. The electrochemical behavior and lithium storage mechanism of SiO2/Ag@PZS-C was also studied. The results reveal that the composite exhibited high specific capacity, stable cycling and superior rate performance. The double modification of silver nanoparticles and polyphosphazene carbon significantly improves the conductivity of silica and reduces the volume change. Moreover, the carbon shell of polyphosphazene facilitated the formation of a stable solid electrolyte interface film (SEI), preventing direct contact between the active material and the electrolyte, thereby substantially enhancing lithium storage performance.